Migration by breeders and floaters of a long-lived raptor: implications for recruitment and territory quality. (September 2017) - Sergio, Fabrizio; Tanferna, Alessandro; De Stephanis, Renaud; Jiménez, Lidia López; Blas, Julio; Hiraldo, Fernando
Abstract : Animal migration is receiving increasing research attention through ever more sophisticated tracking technologies, but the difficulty of trapping nonbreeding floaters has prevented comprehensive tracking studies of how migration varies in young breeders and floaters and whether this has consequences for recruitment (i.e. the transition from floating to breeding). To fill this gap, we satellite-GPS tracked young black kites, Milvus migrans, which start to breed when 1–7 years old. In the prebreeding migration, floaters departed and arrived later than breeders, travelled faster with fewer days at stopovers, as if in a hurry, and suffered more from cross-winds. Survival, recruitment, the territory quality and offspring production of the first reproductive attempt, as well as eventual longevity, declined rapidly with small departure delays. The high payoffs for small gains in timing set young kites on a race for early arrival: individuals improved their departure through early life and late migrants were progressively removed from the population or lingered as old floaters. As a result, individual improvements and selective mortality caused each cohort to progressively split after 3 years of age between a vanishing tail of late floaters and a body of early travelling individuals that then shaped the migratory traits of the adult population. Thus, migration in early life acted as a demographic bottleneck that filtered the transition to the next stage of the life cycle through a carryover effect that linked events operating on different continents. Highlights: Little is known about how nonbreeding, young floaters of long-lived species migrate. In raptorial black kites, floaters departed later for migration than breeders. Floaters migrated faster than breeders but suffered more from adverse winds. Early migration led to improved survival, recruitment, territory quality and longevity. Late migrants were progressively removed by mortality or lingered as old floaters.